2022
DOI: 10.1017/s0950268822001212
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccination rollout in the World Health Organization African region: status at end June 2022 and way forward

Abstract: In October 2021, the WHO published an ambitious strategy to ensure that all countries had vaccinated 40% of their population by the end of 2021 and 70% by mid-2022. The end of June 2022 marks 18 months of implementation of coronavirus disease 2019 (COVID-19) vaccination in the African region and provides an opportunity to look back and think ahead about COVID-19 vaccine set targets, demand and delivery strategies. As of 26 June 2022 two countries in the WHO African region have achieved this target (Mauritius a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 2 publications
3
20
0
Order By: Relevance
“…At the end of December 2021, five countries had achieved the 2021 target (Seychelles, Mauritius, Rwanda, Botswana, and Cape Verde) and 26 countries were yet to reach 10% of their population with the complete primary vaccination series. In response, the WHO Regional Office for Africa (WHO AFRO) conducted a by-country risk assessment of slow vaccination uptake; the assessment prioritized 20 countries, most of which had not reached coverage of 10% of their population having completed the primary vaccination series by the end of December 2021 [ 10 ]. WHO AFRO deployed experts to these countries to support governments’ efforts to scale up COVID-19 vaccinations, as part of its Multi-Partners’ Country Support Teams (MP–CST) Initiative [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of December 2021, five countries had achieved the 2021 target (Seychelles, Mauritius, Rwanda, Botswana, and Cape Verde) and 26 countries were yet to reach 10% of their population with the complete primary vaccination series. In response, the WHO Regional Office for Africa (WHO AFRO) conducted a by-country risk assessment of slow vaccination uptake; the assessment prioritized 20 countries, most of which had not reached coverage of 10% of their population having completed the primary vaccination series by the end of December 2021 [ 10 ]. WHO AFRO deployed experts to these countries to support governments’ efforts to scale up COVID-19 vaccinations, as part of its Multi-Partners’ Country Support Teams (MP–CST) Initiative [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In response, the WHO Regional Office for Africa (WHO AFRO) conducted a by-country risk assessment of slow vaccination uptake; the assessment prioritized 20 countries, most of which had not reached coverage of 10% of their population having completed the primary vaccination series by the end of December 2021 [ 10 ]. WHO AFRO deployed experts to these countries to support governments’ efforts to scale up COVID-19 vaccinations, as part of its Multi-Partners’ Country Support Teams (MP–CST) Initiative [ 10 ]. This initiative has helped targeted countries to diversify service delivery strategies, combining health facility fixed sites with mobile and outreach teams; to carry out mass vaccination campaigns; and to engage more community leaders in demand creation [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Had the targets been reached in these countries, the vaccine impact on disease mitigation is estimated to have been almost doubled [ 5 ]. Impouma et al [ 29 ] reported that by the end of June 2022, the WHO African region had received 625 million doses of COVID-19 vaccines, of which 66% were from COVAX. These doses however, represented only 40% of the doses needed to fully vaccinate 70% of people in all countries, thus compounding the trajectory of regional inequity highlighted by our findings in January 2022.…”
Section: Discussionmentioning
confidence: 99%
“…The result in Kasai Oriental and the pic observed in March 2022 could be explained by the fact that in We performed a comparison of DRC with other nine countries in Central Africa, with the exception of Burundi who have been reluctant to vaccinate [38]. Despite this positive progress, the country has faced several challenges resulting in overall low immunization coverage, making it one of the lowest performing countries in the world for COVID-19 vaccination [39]. DRC has faced numerous challenges in its efforts to combat COVID-19 through vaccination, resulting in an overall low immunization coverage despite receiving 8.2 million doses of vaccines, only 528,000 were administered, representing just 11% of the available doses.…”
Section: Comparison With Vaccination Progress In Neighboring Countriesmentioning
confidence: 99%